Characterization of MOS structure using low-k dielectric methylsilsesquioxane with evaporated and sputtered aluminium gate - Aw, K.C.; Ibrahim, K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The organic methylsilsesquioxane (MSQ) demonstrates low dielectric constant value (2.6) and is promising interlayer dielectric material to reduce the capacitive coupling between metal layers in semiconductor integrated circuits. However, MSQ has lower film density and therefore is more porous than the traditional SiO2 film and could pose reliability issues. This paper is aimed to characterize the MOS capacitor (MOSC) structure with evaporated and sputtered aluminium method deposited on top of spin-on MSQ. Electrical characterization using C-V and I-t measurements during bias temperature stress (BTS) were used to understand the effect of evaporated and sputtered Al on MSQ. The results show that MOSC with evaporated aluminium has lower breakdown voltage and has poor reliability as compared to structures with sputtered aluminium. The high temperature required for evaporation compared to sputtering process caused these, which cause defects at the aluminium/MSQ interface. Sputtered aluminium gate structures demonstrate Al+ injection under high positive voltage stress due to ionization at the Al/MSQ interface.